Development of Sodium Copper Phosphate Cathode for Sodium Ion Battery - Wijesinghe, A. M; Manathunga, C. H; Wanniarachchi, I. L; Alahakoon, T. N; Gamage, S; Perera, S. (International Journal of Advanced Materials Research, 2019)
The technology of Sodium ion battery is expected to replace Lithium-ion battery in near future. The chathodes of Lithium-ion battery are prepared using transition metal composites such as oxides, phosphates and silicates and Sodium-ion batteries are also being tested using such composite chathodes. However, these designed cathodes for sodium-ion batteries show a less capacity. This research was conducted in order to prepare a suitable cathode for a sodium-ion battery. The material was formed through a solid-state reaction of sodium phosphate and copper iodide. The composite which was expected to be formed was sodium copper phosphate. The chathode of the battery was fabricated using mixture of active material, activated carbon and polyvinylidene fluoride (PVDF). Cathode was prepared on an aluminum foil and anode was sodium pressed on a copper plate. The synthesized Material was characterized using powder X-Ray Diffraction (XRD) method. Energy Dispersive X-Ray Analysis (EDEX) was performed in order to identify the chemical composition. Charge discharge curves and cyclic voltammetry was taken to characterize the electrochemical properties of the cell. XRD pattern and EDEX results confirmed that the desired composite was formed. The discharging capacity of the battery was calculated to be 103.12 mA h g-1. The cyclic voltammetry analysis has shown that an oxidation and reduction process occurred while charging and discharging.
Keywords: Sodium-ion Batteries, XRD, Cyclic Voltammetry, Copper Iodide, Phosphates